La transacción extrajudicial para procesos de divorcio por mutuo consentimiento con hijos dependientes - Herrera Chacón, Mercy Johanna (2025)
This study analyses the extrajudicial transaction in divorce proceedings by mutual consent with dependent children in Ecuador, evaluating its effectiveness as an alternative to traditional judicial proceedings. It seeks to identify the benefits and limitations of this mechanism, especially its ability to protect the rights of the minors involved. Throughout the investigation, data collection was used through interviews with notaries, family lawyers and people who have experienced the divorce process by mutual agreement. In addition, documented cases were analysed to evaluate the practical application of the extrajudicial transaction. The data collected allowed to obtain a clear vision of the strengths and weaknesses of this mechanism, as well as the perception of the parties involved. It is necessary to improve current regulations and establish mechanisms that include the participation of specialists who ensure the well-being of minors throughout the process. This will allow the extrajudicial transaction to be an effective and safe tool to resolve divorces with dependent children in Ecuador.